2020
DOI: 10.1002/ijop.12726
|View full text |Cite
|
Sign up to set email alerts
|

Marital interactions and experiences of women living in polygamy: An exploratory study

Abstract: T he study examines interactions and experiences of Bedouin women living in polygamous households in Israel. A mixed-method approach was applied in a two-part study. The quantitative part examined differences in differentiation of self and marital satisfaction between 50 Bedouin women in polygamous marriages and 50 in monogamous marriages. It found that, in polygamous families, women's levels of marital satisfaction were positively related to their I-position and fusion with others and negatively related to em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
7
1
Order By: Relevance
“…Hence, the previous studies were conducted among pregnant, ante-natal and post-natal women. In-addition, polygamous marriage is related to a lack of emotional support, economic dependency, and burden in the care of children, which could be the contributing risk factors to the higher suicidal behavior [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the previous studies were conducted among pregnant, ante-natal and post-natal women. In-addition, polygamous marriage is related to a lack of emotional support, economic dependency, and burden in the care of children, which could be the contributing risk factors to the higher suicidal behavior [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the numbers of wives increase, the challenges of polygamy marriage such as social, emotional, economic crises become significant, which are common reasons for low self-esteem, helplessness, hopelessness, and thoughts of harming self [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, women in polygamous unions desire more children and are less likely to use family planning than women in monogamous unions [34]. Polygamy is likely to create a complex family system that impacts negatively on the way the husband may relate to his wives and children [43], thereby creating distinct household problems, usually stemming from jealousy between co-wives over the husband's affections and resources [2]. In addition to studies documenting polygamy's detrimental effects on wives' health, researchers have identified polygamy as a risk factor for adverse child health outcomes [14] and [48].…”
Section: Contrasting Researchers Of Biblical Blueprint For Marriagementioning
confidence: 99%
“…Polygamy or polygamous marriage refers to a marriage where a spouse has more than one wife, otherwise referred to as polygyny or a spouse having more than one husband, otherwise called polyandry [31]. Polygamy can be defined as a marital relationship involving multiple spouses [2] and [8], comprised of three forms: polygyny refering to one situation where one "husband" is married to two or more wives, while polyandry refers to one wife married to two or more husbands, while polygynandry refers to a scenario where two or more wives are simultaneously married to two or more husbands [9], [12], [29], and [43]. For the interest of simplicity and the purpose of this study which is to emphasize the biblical blueprint for marriage, preferring monogamy as against polygamy, the author shall refer to the three types of polygamy identified above: polygyny, polyandry, polygynandry simply as polygamy.…”
Section: Introductionmentioning
confidence: 99%
“…Polygamy may create a complex family system involving the husband’s relationship and relations between subsequent wives and children [ 1 ]. Polygamous families have distinct household problems, usually stemming from jealousy between co-wives over the husband’s affections and resources [ 2 ].…”
Section: Introductionmentioning
confidence: 99%